Flower‐like MoSe2/C Composite with Expanded (0 0 2) Planes of Few‐layer MoSe2 as the Anode for High‐Performance Sodium‐Ion Batteries. Issue 56 (8th September 2017) - Li, Jie; Hu, Hongxing; Qin, Furong; Zhang, Peng; Zou, Lei; Wang, Haobo; Zhang, Kai; Lai, Yanqing
Abstract: Sodium‐ion batteries (SIBs) have caught considerable attention in last few years owing to the abundance of sodium in comparison to lithium. The commercial graphite anode is demonstrated unsuitable as an anode material for SIBs due to the larger radius of Na + ions, whereas the transition metal dichalcogenides (TMDs) show great potential as anodes for SIBs because of their high achievable capacity. The sluggish kinetics, large volume expansion, and aggregation of those materials however results in severe decay of the electrochemical performance. In this work, a flower‐like MoSe2 /C composite is synthesized with ethylenediamine and cassava starch (denoted as MoSe2 /Ccas ) and designed based on these principles: 1) expand the d‐spacing of (0 0 2) planes of MoSe2 to enhance the kinetics for the intercalation‐deintercalation of Na + ions and 2) embed MoSe2 into the carbon matrix to enhance the conductivity and restrict the volume expansion and aggregation of MoSe2 . As a result, MoSe2 /Ccas exhibits superior cycle performance and rate capability for sodium storage. It shows durable long‐life cycle capability with a reversible capacity of 360 mAh g −1 after 350 cycles at 0.5 Ag −1 . At the current density of 4 Ag −1, the reversible capacity is still maintained at 266 mAh g −1 . Abstract : Layered anodes : A simple one‐pot hydrothermal synthesis followed by heat treatment forms composite flower‐like anode materials of MoSe2 and carbon. Expansion of the interlayer spacing enhances the intercalation kinetics and leads to improved cycling performance of the battery system.